The Meaning Of Family Conflict In Perayaan Mati Rasa Film: A Roland Barthes Semiotic Analysis - Tariq Yazid; Desfina Citra (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
This study aims to analyze the meaning of family conflict in the film